U Uji Aktivitas Antibakteri Ekstrak Etanol Buah Jeruju (Achantus ilicifolius L.) Terhadap Bakteri Staphylococcus aureus Dan Salmonella thypi - Marwah, Jannatul; Hakim, Ali Rakhman; Rohama , Rohama (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: According to WHO (2018), there are cases of antibiotic resistance in 500,000 people with suspected bacterial infections in 22 countries. Jeruju fruit extract (Achantus ilicifolius L.) has antibacterial activity because it contains secondary metabolite compounds such as alkoloids, phenols, flavonoids, tannins, saponins and steroids, which are expected to be an alternative choice in the treatment of bacterial infections. Objective: To identify the antibacterial activity of jeruju fruit extract (Achantus ilicifolius L.) against the bacteria Staphylococcus aureus and Salmonella typhi to determine the MIC and KBM values. Method: Type of research design True Experimental Research Posttest Only With Control Group research design. Antibacterial testing uses disc diffusion and dilution methods. With concentrations of 500mg/ml, 800mg/ml, 1000mg/ml, positive control ciproflaxacin and negative control DMSO. Results: The results of the diffusion test showed that jeruju fruit extract was able to inhibit the growth of bacteria, there was a clear zone around the paper disc at a concentration of 500 mg/ml (9.95 mm). The results of the dilution test have a minimum inhibition at a concentration of 500mg/ml seen in clear media and the ability to kill bacteria at a concentration of 1000mg/ml. It can be said that jeruju fruit extract has MIC and KBM concentration values. Conclusion: Jeruju fruit extract has antibacterial activity with an inhibitory zone at a concentration of 500mg/ml (9.95 mm) and has the power to kill Salmonella typhi bacteria at a concentration of 1000mg/ml.